2014
DOI: 10.1037/a0036489
|View full text |Cite
|
Sign up to set email alerts
|

Peer victimization (and harsh parenting) as developmental correlates of cognitive reactivity, a diathesis for depression.

Abstract: Prior research has shown cognitive reactivity to be a diathesis for depression. Seeking evidence for the developmental origins of such diatheses, the current study examined peer victimization and harsh parenting as developmental correlates of cognitive reactivity in 571 children and adolescents (ages 8-13 years). Four major findings emerged. First, a new method for assessing cognitive reactivity in children and adolescents showed significant reliability and demonstrated construct validity vis-à-vis its relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 79 publications
3
39
0
1
Order By: Relevance
“…The first of these findings replicates the well-established longitudinal effects of harsh parenting and peer victimization on depression in young people (for reviews, see Hawker & Boulton, 2000; McLeod et al, 2007; Reijntjes et al, 2010 Yap, Pilkington, Ryan, & Jorm, 2014). Furthermore, our focus on the additive effects of parent and peer relations is commensurate with various cumulative interpersonal risk models (Cole et al, in press; Epkins & Heckler, 2011). The second of these findings extends previous research, providing preliminary support for the idea that the effect of peer victimization and harsh parenting on depression may be mediated by the adverse effect of these interpersonal risk factors on children’s development of a healthy cognitive style.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of these findings replicates the well-established longitudinal effects of harsh parenting and peer victimization on depression in young people (for reviews, see Hawker & Boulton, 2000; McLeod et al, 2007; Reijntjes et al, 2010 Yap, Pilkington, Ryan, & Jorm, 2014). Furthermore, our focus on the additive effects of parent and peer relations is commensurate with various cumulative interpersonal risk models (Cole et al, in press; Epkins & Heckler, 2011). The second of these findings extends previous research, providing preliminary support for the idea that the effect of peer victimization and harsh parenting on depression may be mediated by the adverse effect of these interpersonal risk factors on children’s development of a healthy cognitive style.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse effects of peer victimization and harsh parenting on depression are well documented (for reviews, see Hawker & Boulton, 2000; McLeod et al, 2007; Reijntjes et al, 2010 Yap, Pilkington, Ryan, & Jorm, 2014). Researchers have even begun to develop models about the especially detrimental effects of cumulative interpersonal risk factors (Cole et al, in press; Epkins & Heckler, 2011). Less well understood, however, are the mechanisms underlying these effects.…”
mentioning
confidence: 99%
“…Yap et al’s (2014) meta-analysis indicated that there is a sound base of evidence supporting a link between parental “aversiveness” -- which includes criticism, punishment, and conflict -- and depression among adolescents. Parental harshness is thought to increase the risk of depressive symptoms through a variety of possible mechanisms, including development of a negative self-concept or self-criticism (Sachs-Ericsson, Verona, Joiner, & Preacher, 2006), cognitive reactivity (Cole et al, 2014), emotional dysregulation (Yap, Schwartz, Byrne, Simmons, & Allen, 2010), or difficulty developing positive social relationships (parental and non-parental).…”
Section: Parenting Stressorsmentioning
confidence: 99%
“…For example, physical and verbal aggression have a stronger association with externalizing symptoms (e.g., delinquency), poor peer relationships, and low prosocial behavior, while indirect aggression is more related to internalizing problems and high prosocial behavior (Card et al, 2008). Verbal aggression, in particular, is rather toxic for cognitive reactivity, such as thinking ill thoughts about themselves (Cole et al, 2014).…”
Section: Subtypes Of Aggressionmentioning
confidence: 99%
“…As a specific oral expression of aggressive behavior, verbal aggression should be distinguished from physical aggression (Chang et al, 2005). In addition, verbal aggression is the most prevalent form of aggression (Wang et al, 2009;Jiang, 2017) and has specific impacts on cognitive reactivity (Cole et al, 2014); thus, researchers should commit more resources to discover the underlying process of verbal aggression (Poling et al, 2019). Few studies have focused on the relationship between verbal aggression and friendship dynamics, which means that friendship dynamics in verbal aggression is less well understood.…”
Section: Potential Limitations In the Existing Literaturementioning
confidence: 99%